Дефібрилятори – складова успіху серцево-легеневої реанімації - Печиборщ, В. П.; Якимець, В. М.; Чернявський, Вадим Віталійович; Вороненко, В. В.; Pechiborshch, V. P.; Yakymets, V. M.; Chernyavskiy, V. V.; Voronenko, V. V. (My University, 2019)
У статтіі знайшло своє відображення життєво важливе питання впровадження дефібриляторів і публічних аптечок з усіма необхідними для надання домедичної та першої медичної допомоги до приїзду бригади екстреної (швидкої) медичної допомоги. Визначені проблемні питання щодо їх впровадження та шляхи їх вирішення. Проаналізовані показники прибуття бригад екстреної (швидкої) медичної допомоги на місце події (виклик) за матеріалами узагальнених звітів центрів екстреної медичної допомоги та медицини катастроф за формою № 22 за 2017–2018 роки. Особлива увага приділена аналізу забезпеченості медичною апаратурою, дефібриляторами та дихальною апаратурою та результатам проведених бригадами екстреної (швидкої) медичної допомоги серцево-легеневих реанімацій на догоспітальному етапі екстреної медичної допомоги у 2017–2018 роках. Визначено рівень знань громадян питань домедичної підготовки та шляхи їх удосконалення. The article found its reflection of the vital issue of introducing defibrillators and public first-aid kits with everything necessary for the provision of pre-medical and first aid to the warrival of the emergency (ambulance) medical Aid Brigade. Identified problematic issues regarding their implementation and the ways of their solution. The indicators of the arrival of the Emergency brigades (ambulance) medical aid to the place of the event (call) are analyzed according to the materials of the generalized reports of the centres of emergency medical care and disaster medicine by Form No 22 for 2017– 2018 years. Particular attention is paid to of the analysis of the provision of medical equipment, defibrillators and respiratory equipment and results of emergency (ambulance) medical care teams of cardio-pulmonary resuscitation at the pre-hospital stage of EMS in 2017–2018 years. The level of knowledge of the citizens about pre-medical training and ways of their improvement are determined.
Defibrillators are a component of the success of cardiopulmonary resuscitation
Keywords: впровадження дефібриляторів; серцево-легеневі реанімаційні заходи; Introducing defibrillators; cardiopulmonary resuscitation